Emotional Experience Writing to Increase Resilience to Stress in Adolescents - Tengku Haqy Nurmaliza; Sri Nugroho Jati; Elly Trisnawati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2022)
Based on the results of initial interviews at the Tunas Harapan and Tunas Melati Orphanages, information was obtained that the problems of the orphaned youth were difficulty adapting at the beginning of their existence in the orphanage, emotional behavior problems, lack of self-confidence, keeping their problems to themselves, and not being able to solve problems that trigger feelings of depression and anxiety cause stress. It indicated the need for an effort to assist adolescents in overcoming problems that cause stress; one of which is through writing activities as a form of conveying ideas. This study aimed to determine the effectiveness of the emotional experience writing (EXPRIT) intervention on the stress resilience of adolescents. The study used a mixed-method approach, with a pre-experimental design and research pattern one-group pretest-posttest. Participants (15 adolescents; 8 boys and 7 girls) were selected using purposive sampling method and stress resilience screening instrument. The results showed that there was no effect of the emotional experience writing (EXPRIT) intervention on stress resilience as indicated by the t count greater than t-table (men: 2,037 > 1,895; women: 2,117 > 1,943), but qualitatively there was a change in the level of stress resilience during the intervention treatment was indicated by an increase in the score of the stress resilience indicator.